Design and analysis of a three-translational parallel mechanism with two translational characteristics - CAI Xiang; QIU Bing; GAO Bo; SHI Zhixin (Jixie chuandong, 2025)
ObjectiveTo solve the problem of the complex control algorithm of the previous three-translation （3T） parallel mechanism in achieving curve trajectory translation, a new type of mechanism that can achieve curve trajectory based on the characteristics of the mechanism itself was proposed.MethodsBased on the design theory of the parallel mechanism derived from the position and orientation characteristics (POC) set equations, the topological properties of the mechanism were analyzed in terms of the POC set, degrees of freedom and coupling degrees; based on the kinematic modeling principle of the topological structure, the analytical positive and analytical inverse position equations of the mechanism were obtained, and the correctness of the positive and inverse solution equations was verified. SolidWorks software and Matlab software were used to verify that the mechanism had different moving motion characteristics under different drive forms.ResultsFor traditional 3T parallel mechanisms that only enable straight-line motions, achieving curved translations in two directions necessitates complex algorithms to fit curves through multiple straight-line movements. In contrast, the proposed mechanism can achieve curved translations simply by altering the motion velocities of the driving joints.